Determining the Viscosity Coefficient of Fluids Using a Simple Viscosity Practical Tool Aided by Arduino Uno and a Magnetic Sensor - Aris Doyan; Bung Ashabul Qahfi; Susilawati Susilawati (AMPLITUDO : Journal of Science and Technology Innovation, 2023)
This study aims to design and create fluid viscosity test equipment in the form of used oil, sunlight, soklin, liquid rinso, and harpick. The working principle of the viscometer uses a free-falling ball system according to Stokes' law principles. The stages in making a viscometer are designing a tool model, designing hardware and software, designing a mechanical system and testing. Designing hardware includes hall effect magnet sensor, arduino uno, lCD, and power supply. The software uses the Arduino IDE-assisted programming language. The design of the tool includes supports, boxes, magnets, and glass tubes. the test was carried out by measuring the viscosity coefficient of used oil, sunlight, so klin, rinso, and harpick. The viscosity coefficients of used oil, sunlight, floor soklin, liquid Rinso, and harpick from the test results have been able to be measured with a viscometer that has been made.